Does True Syntax or Simple Auditory Object Support the Role of Skylark Song Dialect? - Briefer, Elodie F.; Rybak, Fanny; Aubin, Thierry (WBI Studies Repository, 2013)
Parallels between birdsong and human language are numerous and include particular temporal arrangements of acoustic units and the existence of dialects. In animal communication, modifications of the temporal ordering of existing acoustic units have rarely been clearly linked with changes in information content, particularly in a natural environment. Here, we show that the organization of birdsong units (‘syllables’) in sequences supports interindividual relationships within skylark communities. We manipulated the temporal arrangement of song dialect variants (‘shared phrases’) in the skylark, Alauda arvensis, a songbird with a very large repertoire of syllables and complex song. When tested with playback experiments performed in the field, skylarks were able to perceive subtle differences in the ordering of syllables. Modifications of the syllable ordering within shared phrases changed the information content from ‘group member’ to ‘unfamiliar individual’ and induced more aggressive reactions than shared phrases with a preserved syllable arrangement. Shared phrases often varied between individuals in the number of successive repetitions of similar syllable types, but were very consistent in terms of syllable type ordering. Our results indicate that skylarks rely not simply on the composition in syllable types of shared phrases to recognize group members, but on syllable type ordering. Shared phrases could be perceived by birds as ‘auditory objects’ embedded within songs. Alternatively, birds might identify incorrect phrases using grammatical rules governing the succession of syllables composing the phrases shared by their group. The presence of between-individual variation in phrase length, associated with consistent syllable type ordering revealed by our analysis, suggests that the latter hypothesis is more likely. Our results show that birds perceive disruptions in the natural temporal pattern of song units, and that this temporal pattern is behaviourally salient and carries information.